A two-way pedagogical action. Secondary education at the Institut-Escola de la Generalitat and the Pedagogy Seminar of the University of Barcelona - Corell Domenech, Mavi (CIAN-Revista de Historia de las Universidades, 2023)
The Institut-Escola de la Generalitat (1931-1939) formed part of the project for the renewal of the education in Catalonia during the Second Spanish Republic (1931-1939). This high education center was conceived as a pedagogical experiment, together with the Escola Normal de Generalitat (1931-1939), for the introduction in the classroom of new teaching methods, coeducation, and the Catalan, in addition to Spanish. This project ended with the victory of fascism in Spain after the Civil War (1936-1939).In this article we address the relationships between the Institut-Escola, directed by Josep Estalella, and the Seminari de Pedagogia of the University of Barcelona, directed by Joaquim Xirau. The coordination between both centers led to the training of future secondary school teachers in the new pedagogical trends being promoted by the Institución Libre de Enseñanza and its Instituto-Escuela of Madrid.In this paper we study the courses that the Seminary and the University of Barcelona taught, and we focus on two that were related to the natural sciences: the course on the teaching of physical-chemical sciences by Estallella, and the botany course given by Pius Font i Quer, professor at the Faculty of Pharmacy. Three teachers from the Institut-Escola participated in the botany course, including Àngels Ferrer i Sensat. We conclude that teacher training took two directions, that of the Institut-Escola as a practical laboratory of pedagogical experiences, and that of the University as an academic center of pedagogical knowledge.
Keywords: Institut-Escola; Seminari de Pedagogia; University of Barcelona; Josep Estalella; Pius Font i Quer; secondary education